PENGARUH PEMBELAJARAN ONLINE DAN IKLIM KELAS TERHADAP KOHESIVITAS SISWA KELAS XI PADA MATA PELAJARAN SOSIOLOGI DI SMA GEMBALA BAIK PONTIANAK - Patrisia Rahayu Utami; Yohanes Bahari; Amrazi Zakso (Universitas Tanjungpura, 2021)
AbstractThe research aims to find out the image of online learning, class climate and the cohesivity of students on the xi class sociology subjects at the good shepherd's pontichildren high school. The research USES a kind of ex-post facto with the pattern the dominant-less intrinsidesign from creswell. The population in the study was the xi class xi majoring in the ips high school good shepherd the pontifex number 149. The sample retrieval technique USES a simple random sampling with the number of samples 109 trainees. These research instruments use online learning angkets, class climate angkets and student cohesics. There are three stages of data analysis used in research: descriptive statistical analysis, the testing of requirements for analysis and the testing of hypotheses. Based on the results of descriptive analysis, the average online learning score of 59.05 falls in low category, the class's average score of 60.59 falls on category well, the 65.21 student cohesivitas average score of 65.21 falls in high category. With the regression with the multiple distribution of statistics that follow is an f-test, at a price of 32.401 that is significant in 0,000 (elevation <0.05), thus can be concluded ho is rejected, which means there is a positive and significant influence between online study and classroom climate on the xi student cohesivitas at good shepherd high school.Keywords: Online Learning, Class Climate, Student Cohesivitas